Avaliação de carvões ativados de diferentes naturezas para adsorção de corante têxtil - Cionek, Caroline Apoloni (2013)
: Textile industries use large quantities of water in beneficiation processes, therefore, that this water can be poured into rivers it must be treated, not to harm the environment. There are various types of effluent treatment, however, the adsorption process has shown significant results. In order to perform a project of treating textile effluents by adsorption is necessary to know some information about the removal capacity and adsorption kinetics. Thus, the aim of this thesis was to study the use of coals of different natures, made from byproducts such as bone, coconut shell, coconut and babassu coconut palm to the selective removal of textile dye Reactive Blue BF-5G, by batch adsorption process, checking the characteristics of the adsorbent, the process temperature and the addition of sodium chloride in the dye solution. The adsorbents were characterized to determine the zero point of charge, the textural properties of adsorption and desorption of N2, infrared spectroscopy and Boehm method. To the point of zero charge of carbons Babassu, Coconut Shell, Palm and Bone found values of 7.4, 9.2, 7.6 and 7.5, respectively. The N2 adsorption showed that the coals Babassu, Coconut Shell and Palm are predominantly microporous, with contribution of mesopores, while Bone showed characteristics of mesopores. The method of Boehm shows that charcoal from coconut shell was presented the highest basicity and lower acidity, while the remaining coals showed little difference between basic and acid groups. Infrared spectroscopy showed that activated carbons Babassu, Coconut and Palm Bark showed similar bands, corresponding to the presence of hydroxyl groups, aldehyde and ketone. The bone char coal showed different behavior, with several bands, mostly attributed to the structure of hydroxyapatite. For the tests the adsorption equilibrium time the process was approximately 18 hours for all coals. The pseudo first-order models, pseudo second order and intraparticle diffusion were fitted to experimental data to describe the adsorption kinetics, and the model pseudo second order was the model that best fit the data. The adsorption isotherms were adjusted for Langmuir, Freundlich, Sips, Toth, and Redlich Peterson and Radkee Praunsnitz. The best fits were obtained with the Sips and Freundlich models. Coal Bone showed the highest amount of dye adsorbed (142.3 mg g-1), followed by coal Babassu (76.21 mg g-1), Peel Coco (75.35 mg g-1) and Palm (68.74 mg g-1). The evaluation of the addition of salt in the adsorption showed that the presence of NaCl to an increase in dye adsorption capacity of 142.2 to 262.4 mg.g-1 for activated carbon bone, at 40 °C. Thus, the cations Na+ salt adsorbate can bind to negative ionic repulsion reducing or neutralizing the negative charges of the coal, decreasing the repulsion surface and the adsorbate, thereby increasing the amount of adsorbed molecules. The thermodynamic properties ∆H°, ∆G° and ∆S° were evaluated and showed that adsorption of the dye Reactive Blue BF-5G. The coals Babassu and Coconut Shell have a negative ∆G°, characteristic of spontaneous process. They also have features to endothermic process all coals, as evidenced by the values of ∆S° increasing with increasing temperature, showing that this favors the adsorption process.